PERANCANGAN SISTEM MONITORING ALAT DAN BAHAN PRAKTIKUM PADA PERKULIAHAN BERBASIS WEB: LAB TOOLS, MONITORING SYSTEM, SYSTEM DESIGN, WEB PROGRAMMING - Ayu Armi, Puspita; Meilano, Rezagi (FORTECH (Journal of Information Technology), 2018)
Lab tools and materials are very important in supporting practical activities. The process of borrowing lab tools and materials at Electrical Installation Laboratory in Politeknik Jambi is still done manually by using paper which make it difficult to monitor the availability. For that reason we need a system that can help that process, namely the Monitoring System Lab Tools and Materials. It was developed based on web and client servers to support the flexibility of the designed system. The system was created by using the PHP programming language and MySQL database. The research resulted  in a software monitoring system tools and lab materials in lectures that can be accessed by lecturers and head of laboratory. The system makes it easier to borrow lab tools and materials and also for the head of laboratory to monitor any information about the availability of tools and materials in the laboratory.